Social Equity and Popular Culture: Gender and Gender Identity on TV. (4th May 2021) - Borry, Erin L.
Abstract : Social equity is an important element of public administration and policy, and theoretically is as important as economy, efficiency, and effectiveness by the National Academy of Public Administration. Social equity, which focuses on fair and just processes and policy outcomes, has largely related to race and gender, but its application to gender identity is coming to the fore as various states and localities adjust their policies related to identification. Advancing social equity requires difficult conversations as well as organizational and policy efforts. This article explores the role of social equity conversations—nervous conversations—and how they are portrayed on television. Two series of nervous conversations related to gender and gender identity, in Modern Family and Grey's Anatomy, are analyzed via Gooden's "Race Talk Strategies" framework. This analysis considers the effectiveness of these conversations as well as how portrayal of these conversations may influence social equity in the real world.